On the Nature of Kink MHD Waves, Vorticity and Compressibility Versus Restoring Forces - Karam Bahari (Iranian Journal of Astronomy and Astrophysics)
In order to study the nature of kink MHD waves, zero beta plasma in a thin twisted magnetic-flux tube is considered. We use two parameters, the ratio of restoring forces and the ratio of the parallel vorticity to the compressibility to study the effect of magnetic twist on the nature of kink waves. Our aim is to invstigate whether the nature of the wave obtained from studying these two parameters are the same or not. The two parameters give two different twist parameters in which the wave becomes purely Alfvénic. The first parameter indicates that both in the internal and external regionsof the tube, the wave can become purely magnetoacostic but the second parameter indicates that the wave can become magnetoacostic only in the external region of the tube. Our conclusion is that the two parameters are not equivalent for determining the nature of the wave.